Discrete-time linear systems with desired poles and zeros of the transfer matrices - Kaczorek, Tadeusz (1932- ); Sajewski, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
Methods for the design of discrete-time linear systems with desired poles and zeros of their transfer matrices are proposed. Conditions for the existence of the solution to the problem and the procedures for computation of the desired matrices are given. Reduction of the systems with controllable and observable pairs to those with nilpotent matrices is analysed. The procedures are illustrated by simple numerical examples of linear discrete-time systems.
Keywords: design method; linear systems; discrete-time systems; nilpotent system; pole; zero; transfer matrix